2015
DOI: 10.1089/hgtb.2015.051
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cesium Chloride- and Iodixanol-Based Purification of Recombinant Adeno-Associated Viral Vectors for Preclinical Applications

Abstract: Cesium chloride (CsCl)- and iodixanol-based density gradients represent the core step in most protocols for serotype-independent adeno-associated virus (AAV) purification established to date. However, despite controversial reports about the purity and bioactivity of AAV vectors derived from each of these protocols, systematic comparisons of state-of-the-art variants of these methods are sparse. To define exact conditions for such a comparison, we first fractionated both gradients to analyze the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 28 publications
2
118
0
3
Order By: Relevance
“…51,88 The present study included, consistent reproducibility of the predicted packaging ratios in AAV2, AAV8, and AAV9 shows that the process is serotype-independent; production levels at surface areas ranging from 148 to 6,320 cm 2 using roller bottles or flasks highlight the scalability and flexibility in manufacturing; purification of copackaged vectors are not affected whether performing cesium-chloride or iodixanol centrifugation; and careful titration of the expression plasmids results in consistent ratios across preparations. 51,88,92 Rearrangement of the plasmid genome brought on by homologous recombination during packaging is a concern but seems to occur at a negligible rate as the output ratios are highly consistent of the predicted ratios. 51 Once the manufacturing process is defined, the copackaged candidate vector can therefore be treated as a single product for toxicology, stability, sterility, and release testing as performed for any current AAV clinical trial rather than as two independent products.…”
Section: Discussionmentioning
confidence: 76%
“…51,88 The present study included, consistent reproducibility of the predicted packaging ratios in AAV2, AAV8, and AAV9 shows that the process is serotype-independent; production levels at surface areas ranging from 148 to 6,320 cm 2 using roller bottles or flasks highlight the scalability and flexibility in manufacturing; purification of copackaged vectors are not affected whether performing cesium-chloride or iodixanol centrifugation; and careful titration of the expression plasmids results in consistent ratios across preparations. 51,88,92 Rearrangement of the plasmid genome brought on by homologous recombination during packaging is a concern but seems to occur at a negligible rate as the output ratios are highly consistent of the predicted ratios. 51 Once the manufacturing process is defined, the copackaged candidate vector can therefore be treated as a single product for toxicology, stability, sterility, and release testing as performed for any current AAV clinical trial rather than as two independent products.…”
Section: Discussionmentioning
confidence: 76%
“…However, the widespread use of rAAV vectors is limited by the time and expense needed to produce them. The current methods for purifying rAAV utilize gradients of either iodixanol or cesium chloride [13][14][15][16][17]. These methods require the use of specialized centrifuges and expensive reagents which can prevent laboratories lacking the proper equipment or funding from producing rAAV in-house.…”
Section: Introductionmentioning
confidence: 99%
“…Ultracentrifugation is a popular choice for the purification of adeno‐associated virus (AAV) gene therapy vectors. A recent study showed a 60% yield for CsCl and a 65% infectious units recovery for an iodixanol based AAV purification method . While yield and purity can be high with ultracentrifugation, the lack of scale‐up options makes it unfeasible for long‐term, high volume production.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed a 60% yield for CsCl and a 65% infectious units recovery for an iodixanol based AAV purification method. 5 While yield and purity can be high with ultracentrifugation, the lack of scale-up options makes it unfeasible for long-term, high volume production. A more scalable method of virus particle purification is ultrafiltration.…”
Section: Introductionmentioning
confidence: 99%